2016
DOI: 10.1177/1203475416648323
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Psoriasis, Therapies, and Suicide

Abstract: Many chronic medical disorders are associated with psychiatric morbidity. Yet the psychological burden of these disorders often goes unnoticed. In dermatology, psoriasis has a higher association with psychiatric illness, including depression and suicide risk, compared with many other conditions. Studies suggest that effective treatment of psoriasis results in the improvement of psychiatric morbidity, particularly depression and anxiety. New biologic treatments for psoriasis may offer help beyond clearing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 97 publications
(234 reference statements)
1
42
0
Order By: Relevance
“…In the VOYAGE 2 study, a considerable proportion of patients had anxiety (approximately 40%) or depression (approximately 30%) at baseline as measured by the HADS, demonstrating the significant burden of psychiatric disorders for patients with psoriasis. These rates are generally comparable to those reported in other psoriasis studies and higher than the rates reported globally in patients without psoriasis . Although there is no formal definition of clinically meaningful improvement in HADS scores, our findings show significant improvements in both anxiety and depression scores with guselkumab treatment compared with placebo at weeks 8 and 16 ( P < 0.001 for all).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the VOYAGE 2 study, a considerable proportion of patients had anxiety (approximately 40%) or depression (approximately 30%) at baseline as measured by the HADS, demonstrating the significant burden of psychiatric disorders for patients with psoriasis. These rates are generally comparable to those reported in other psoriasis studies and higher than the rates reported globally in patients without psoriasis . Although there is no formal definition of clinically meaningful improvement in HADS scores, our findings show significant improvements in both anxiety and depression scores with guselkumab treatment compared with placebo at weeks 8 and 16 ( P < 0.001 for all).…”
Section: Discussionsupporting
confidence: 87%
“…The burden of psoriasis has even been categorized as a cumulative disability, which can negatively impact a patient throughout their lifetime . Patients with psoriasis have a significantly higher prevalence of psychiatric disorders, including anxiety and depression, compared with the general population and with other dermatology patient populations . In addition, psoriasis patients with psychiatric disorders have higher healthcare costs than psoriasis patients without these disorders …”
Section: Introductionmentioning
confidence: 99%
“…This risk was likely exacerbated by the socioeconomic disadvantage prevalent in this patient population . Moreover, post‐marketing investigation which did not exclude patients who had a present or past medical history of mental disorder demonstrated that suicide ideation, attempted suicide and its completion occurred in patients receiving adalimumab, etanercept or infliximab . Papp et al .…”
Section: Safety Concerns Specific For Each Biologicmentioning
confidence: 98%
“…reported that brodalumab improved depression and anxiety scores over 12 weeks. Although concerns have been raised regarding the potential link between brodalumab in psoriatic patients and suicide, current published work provides no evidence to support this association . However, brodalumab was approved by the US Food and Drug Administration in February 2017, which has warned of the increased risk of suicidal ideation and behavior.…”
Section: Safety Concerns Specific For Each Biologicmentioning
confidence: 99%
“…People with psoriasis may experience significant stigmatization and negative effects on relationships, employment opportunities and social activities, and the cumulative effect may be failure to achieve a ‘full life potential’ . Accessing timely effective care may reduce the development of comorbidities, including depression and suicide risk, and associated healthcare burden …”
mentioning
confidence: 99%